A teacher's guide to 14-19 policy and practice - Senior, Lynn (Routledge/Taylor and Francis Group, 2017)
"This concise and up-to-date guide to 14-19 education aims to demystify recent policy initiatives in the sector to help teachers and practitioners understand the rationale for the qualifications on offer and support them in their daily practice. Offering lots of additional guidance, it will help teachers to access the ongoing support that is available and develop their own professionalism. A Teacher's Guide to 14-19 Policy and Practice considers the types of knowledge needed to teach vocational education and offers a wealth of strategies for effective learning, teaching and assessment to ensure that all students achieve and progress. It also explores the ways that teachers can follow the Information, Advice and Guidance (IAG) standards to develop employability in the classroom and help students gain the skills they will need to manage their personal lives and careers in the future"--Publisher's description